Peran Kepemimpinan dan Kompetensi SDM dalam Meningkatkan Kinerja Karyawan Kementerian PUPR - Lutvie Fitral Pratama; Nur Asni Gani (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of leadership and competence on employee performance at the Ministry of PUPR, especially at the Directorate General of Human Settlements. This research uses a quantitative approach with a survey method through distributing questionnaires to 61 respondents who are employees within the Ministry of PUPR. The data obtained were analyzed using multiple linear regression analysis using SPSS 22.0. The results showed that leadership and competence have a positive and significant effect on employee performance. Effective leadership is able to increase employee motivation and work direction, while high competence allows employees to complete tasks more efficiently and with quality. The coefficient of determination (R²) value of 0.707 indicates that 70.7% of variations in employee performance can be explained by leadership and competence, while the rest is influenced by other factors not examined in this study. The implication of this study is the importance of developing effective leadership and improving employee competencies through training and skills development. In addition, management needs to provide constructive feedback and create a supportive work environment to improve employee performance. This study also has limitations, such as limited samples and research locations, so it is recommended that future research expand the scope of samples and variables studied.